The Role of Language in the Formation of crosscultural Bonds - Gulnora Siyaeva (Peerian Journals Publishing, 2025)
The word “culture” has different meanings in different disciplines, and as part of our socialization in life, by means of culture each of us learns ways to communicate, move, think, use objects and tools in the world. This article addresses issues such as language, culture, typology of cultures, types of communication, oral communication, cultural adaptation, and intercultural barriers and conflicts. Linguoculturological issues related to the concept of language and culture, which are currently attracting everyone’s attention in linguistics, have been studied by many scholars, but have not been resolved. It is noteworthy that this article focuses on this issue - a new field of linguistics - intercultural relations in the process of teaching a foreign language
Keywords: intercultural relations; culture; social communication